Numerical study of a methane jet diffusion flame in a longitudinal tube with a standing wave - Tarique, Ashique Akram (2018)
Flame stability plays an important role in a combustion/propulsion system, which involves the interaction between flow, acoustics, and flame. Although intensive studies have been carried out to investigate the flame-acoustic interactions, the jet flame excited by standing waves formed in a longitudinal tube has not received much attention. In this work, a methane-burnt (CH4) jet diffusion flame in a longitudinal tube with a standing wave produced from a loudspeaker is studied numerically. 2-D unsteady RANS simulations are performed by using ANSYS FLUENT with the standard k−ɛ turbulence model and a one-step Eddy-Dissipation combustion model. The acoustic fluctuations are generated by using User Defined Functions. The numerical results show that a longitudinal standing wave can be successfully obtained in the tube by the numerical method, and both the acoustic velocity node and antinode can be observed. It is also found that the jet flame characteristics are highly sensitive to its axial location in the tube when the standing wave is present. The flame is unsteady when it is located at the velocity antinode where large velocity fluctuation exists. When the jet is placed at acoustic velocity nodes, however, the flame is relatively steady. Although the minimum velocity fluctuation at the two velocity nodes is almost at the same level, different flame temperatures are observed, due to the different turbulence kinetic energy.